Ergonomics Improvement in Ceramic Production through Hydraulic Tool Design: A Rapid Entire Body Assessment and Quality Function Deployment - Putri Noviana Nih Pratama; Sido Dea Auvia; Anggita Indriyanti; Agung Ramadhani (Jurnal INTECH Teknik Industri Universitas Serang Raya, 2026)
This study addresses ergonomic and productivity challenges in Indonesia's ornamental ceramic MSMEs. Artisans often rely on traditional tools, resulting in high musculoskeletal risks and inefficient production. Using the Nordic Body Map (NBM) and REBA, this study identified a "very high risk" posture (REBA score of 13). Quality Function Deployment (QFD) was then employed to design an ergonomic hydraulic press based on worker anthropometry, featuring a table height of 104.7 cm and a machine height of 130.75 cm. The results demonstrate a significant reduction in production cycle time, as the dual-mold hydraulic system allows for the simultaneous pressing of two faces, effectively replacing time-consuming manual processes. Furthermore, the design minimizes non-value-added work elements by eliminating the need for gradual manual clay filling. This transition from a crouching to a neutral standing posture not only ensures artisan safety by lowering physical strain but also significantly increases output capacity. This study proves that integrating ergonomic specifications with mechanization is a vital catalyst for increasing operational efficiency and business sustainability in small-scale industries.